2011
DOI: 10.1016/j.hal.2010.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Review of Florida red tide and human health effects

Abstract: This paper reviews the literature describing research performed over the past decade on the known and possible exposures and human health effects associated with Florida red tides. These harmful algal blooms are caused by the dinoflagellate, Karenia brevis, and similar organisms, all of which produce a suite of natural toxins known as brevetoxins. Florida red tide research has benefited from a consistently funded, long term research program, that has allowed an interdisciplinary team of researchers to focus th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
152
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 203 publications
(153 citation statements)
references
References 109 publications
1
152
0
Order By: Relevance
“…Our research comprised significant spatial and temporal extensions of earlier work that demonstrated the relationships between FRT bloom events and human respiratory and digestive illnesses in Sarasota County, Florida (Kirkpatrick et al 2004;Backer 2009;Fleming et al 2011). …”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…Our research comprised significant spatial and temporal extensions of earlier work that demonstrated the relationships between FRT bloom events and human respiratory and digestive illnesses in Sarasota County, Florida (Kirkpatrick et al 2004;Backer 2009;Fleming et al 2011). …”
Section: Discussionmentioning
confidence: 82%
“…Although some authors have pointed to FRT blooms as a source of digestive illnesses (Kirkpatrick et al 2006(Kirkpatrick et al , 2010Backer 2009;Fleming et al 2011), this effect has been discounted largely because of an effective program to monitor and manage SHAs to mitigate the harvesting of shellfish potentially contaminated with brevetoxins. Because the pathway that brevetoxins take from K. brevis to humans is uncertain, our result that digestive illnesses are related to FRT bloom events was surprising.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations